2021
DOI: 10.4103/ijo.ijo_1511_21
|View full text |Cite
|
Sign up to set email alerts
|

Retrobulbar injection of amphotericin B using intravenous cannula for post-COVID-19 rhino-orbital mucormycosis

Abstract: Rhino-orbital mucormycosis has seen a huge resurgence in patients post COVID-19 infection. In patients with minimal orbital disease and especially with preserved vision, retrobulbar injections of amphotericin B can be of great help in controlling the disease. Instead of giving daily injections of amphotericin B using needles every time, we used an 18-gauge intravenous (IV) cannula with injection port and suture holes to deliver the amphotericin into the orbital space for a period of 5 days. Patients were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(21 reference statements)
0
3
0
1
Order By: Relevance
“…Murthy et al . [ 59 ] described an alternative technique of retrobulbar injections using an intravenous cannula to stop the orbital disease progression in ROCM. Retrobulbar injection of AMB is an off-label procedure and has an associated risk of significant complications.…”
Section: Treatmentmentioning
confidence: 99%
“…Murthy et al . [ 59 ] described an alternative technique of retrobulbar injections using an intravenous cannula to stop the orbital disease progression in ROCM. Retrobulbar injection of AMB is an off-label procedure and has an associated risk of significant complications.…”
Section: Treatmentmentioning
confidence: 99%
“…In 1 study, the drug was delivered in the orbital cavity for 5 days by insertion of an intravenous cannula. 32 In another study, combined intravitreal and retrobulbar injections were done in patients with endophthalmitis. 27 Although the outcomes of protocols for retrobulbar injections among the reviewed studies cannot be compared with each other by statistical analysis due to inadequate data, but these studies revealed that the effectiveness of the injections in reducing signs of orbital disease is higher among cases with minimal orbital involvement, and that advanced cases needed more injections exhibiting poorer responses to the injections.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to its high potential to induce nephrotoxicity, continuous monitoring of the patients is necessary. Also, combination therapy with echinocandins and amphotericin B is accepted as second-line therapy (21). Other medications such as Isavuconazole or Posaconazole have been used in cases with invasive mucormycosis (22).…”
Section: Discussionmentioning
confidence: 99%